Aplikasi Pendekatan Theory of Constraints pada Maksimasi Throughput Produksi - Kristiana, Leo Rama; Sunarni, Theresia (Jurnal Media Teknik dan Sistem Industri, 2018)
PT XYZ is a manufacturing company that produces various furniture products. The company has two product categories, first category A (as standard products) with production system is make to stock the second is category B (custom products) with production system is make to order. Production time products category B is more than longer than production time product category B. Production department’s PT XYZ arise problem when face high demand. Limitations of production’s resources cause bottleneck in lines production and inability to meet demand. In addition, inaccuracies in allocating limited resources will causing descent of throughput. Optimization of limited resources needs to be done to reach the maximum throughput. This research was conducted to find out the production resources that become constraintss in fulfilling demand, the number of each type of product must be produced at the existing capacity to achieve optimal throughput and identify and analyze solutions to problems of limited production resources. The results of the study conclude that the production resources that become constraintss are man power and man hours. The maximum throughput that can be achieved by PT XYZ by optimizing the existing available resources is Rp. 819,148,490, and there are two types of products that cannot be fulfilled. Increased production capacity can be done with several alternatives, such as over time hours, out sourcing operators (freelancers), subcontracting of production, adding man power with recruitment of new operator and their combinations. The optimal throughput is Rp 1,056. 763,100 could be obtained from using alternative resource from recruiting new operator and combination with over time capacities.